Relationship between oral hypofunction and medical expenditure in older adults in Japan - Takatoshi Hiroshimaya; Yoshiaki Kawagoe; Kazuto Fukuhara; Hiroshi Ijichi; Naofumi Tamaki (Scientific Reports)
Abstract This study aimed to analyze the impact of poor oral function on medical expenditures among older adults. We diagnosed oral hypofunction based on dental data obtained from oral health examinations and examined its association with several annual medical expenditures. Compared to individuals without oral hypofunction, those with oral hypofunction incurred higher total, outpatient medical, inpatient medical, dental, dispensing medical, and lifestyle-related medical expenditures. Those with high medical expenditure costs were significantly more likely than those without to be 80 years old, male, with oral hypofunction, poor oral hygiene, xerostomia, poor lip closure, physical frailty, mental frailty, and subjective poor health. Logistic regression analysis indicated that oral hypofunction was significantly associated with total medical, inpatient medical, dental outpatient, dispensing medical, and lifestyle-related medical expenditures, compared to those without oral hypofunction (p < 0.05). Additionally, every increase in the number of items with declined oral function and total medical, dental, and dispensing medical expenditures increased significantly (p < 0.01). The results of this study suggest an association between oral hypofunction and several medical expenditures. The prevention and early detection of oral hypofunction would reduce not only dental but also medical expenditures by the maintenance of good health.